Toughening and functionalization of bioactive ceramic and glass bone scaffolds by biopolymer coatings and infiltration: a review of the last 5 years. (January 2014) - Philippart, Anahí; Boccaccini, Aldo R; Fleck, Claudia; Schubert, Dirk W; Roether, Judith A
<x xml:space="preserve">Abstract</x> Inorganic scaffolds with high interconnected porosity based on bioactive glasses and ceramics are prime candidates for applications in bone tissue engineering. These materials however exhibit relatively low fracture strength and high brittleness. A simple and effective approach to improve the toughness is to combine the basic scaffold structure with polymer coatings or through the formation of interpenetrating polymer-bioactive ceramic microstructures. The polymeric phase can additionally serve as a carrier for growth factors and therapeutic drugs, thus adding biological functionalities. The present paper reviews the state-of-the art in the field of polymer coated and infiltrated bioactive inorganic scaffolds. Based on the notable combination of bioactivity, improved mechanical properties and drug or growth factor delivery capability, this scaffold type is a candidate for bone and osteochondral regeneration strategies. Remaining challenges for the improvement of the materials are discussed and opportunities to broaden the application potential of this scaffold type are also highlighted.